Physical and Thermal Properties of Untreated and Chemically Treated Rice Husk - Jha, S K; Singh, Amar (Journal of Agricultural Engineering, 2007)
Moisture dependent physical and thermal properties of untreated, acid and alkali treated rice husk were evaluated in the moisture range of 5 to 35% (db). Moisture content had significant effect on the physical and thermal properties of rice husk. A significant difference in each property was found between untreated, acid and alkali treated husk. Bulk density of untreated, acid treated and alkali treated husk varied from 98-106.5, 91.5-102 and 59-64 kg/m3 whereas the corresponding values of true density, angle of repose, specific heat, thermal conductivity and thermal diffusivity varied as 1009-1054, 1004-1054,969-996 kg/m3; 47-53.8, 47.2-52.4, 46.9- 51.5 degrees; 1.098-2.754, 0.976 to 2.548 and 0.875 to 2.33 kJ/(kg.K); 0.024 to 0.099, 0.023 to 0.092 and 0.026 to 0.102 J/(s.m.K), respectively. The bulk density, true density, angle of repose, specific heat, thermal conductivity and thermal diffusivity increased linearly with increase in moisture content whereas the porosity decreased linearly. The values of bulk density, true density, angle of repose and specific heat were higher for untreated rice husk and were followed by acid and a1kali treated husk. However, the values of thermal conductivity and thermal diffusivity were higher for alkali treated husk and were followed by untreated and acid treated husk.